Penerapan Model Financial Engineering dengan Cost Benefit Analysis untuk Pengelolaan Investasi Rutin Aset Bergerak di PT XYZ - Endah Setyowati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to apply a financial engineering model with a cost-benefit analysis (Cost Benefit Analysis) in the management of routine investments in movable assets at PT XYZ. The main objective of this research is to provide a systematic and quantitative framework to assist management in making optimal investment decisions. The theory used in this study includes the basic concepts of financial engineering and cost-benefit analysis. Financial engineering provides mathematical and statistical tools and methods to address complex financial problems, while cost-benefit analysis is used to evaluate the advantages and disadvantages of various investment options. The research method used is a case study at PT XYZ. The data collected includes historical financial data, projections of income and expenses, information regarding routine investments made by the company, and interviews with company informants related to cost-benefit analysis. The analysis is conducted using cost-benefit analysis on the aspects of the time value of money, cost analysis, and financial risk by comparing various investment scenarios of movable assets on lease and purchase options. The results of this research are expected to provide recommendations that can be implemented by PT XYZ to improve the efficiency and effectiveness of the company's movable asset investment management and optimize the allocation of the company's financial resources.